1999
DOI: 10.1046/j.1439-0450.1999.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of a Live Vaccine against Porcine Reproductive and Respiratory Syndrome in Fattening Pigs

Abstract: A live vaccine based on a European isolate of porcine reproductive and respiratory syndrome virus (Porcilis PRRS) was tested in this study in order to determine the protection of fattening pigs against the respiratory form of the syndrome under field conditions. Ten thousand pigs in an infected farm were vaccinated against PRRS virus at the age of 6 weeks and were compared with non‐vaccinated pigs with respect to their health status, mortality, performance parameters (average daily gain, average daily feed int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
2
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 6 publications
2
11
2
4
Order By: Relevance
“…However, vaccinated animals did not show any significant reduction of PRRSV viremia compared with control animals under field conditions in previous studies (16,17) or the present study. Similarly, no change in PRRSV viremia was observed in an experimental challenge study with another modified live PRRS vaccine based on the type 2 genotype, although vaccination did improve growth performance and reduce lung lesions (21).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…However, vaccinated animals did not show any significant reduction of PRRSV viremia compared with control animals under field conditions in previous studies (16,17) or the present study. Similarly, no change in PRRSV viremia was observed in an experimental challenge study with another modified live PRRS vaccine based on the type 2 genotype, although vaccination did improve growth performance and reduce lung lesions (21).…”
Section: Discussioncontrasting
confidence: 77%
“…Clinical respiratory signs were also improved in vaccinated animals on all 3 farms. There is minimal peer-reviewed information on the efficacy of the PRRSV vaccines based on the type 2 genotype under field conditions (16,17). To our knowledge, this is the first field study of the new modified live PRRS vaccine based on the type 2 genotype.…”
Section: Discussionmentioning
confidence: 99%
“…In the presented study good protection against PRRSV and reduction of economic losses is clearly recognizable by the higher ADWG in the vaccinated groups. This is concurrent with studies which have shown the positive effect of a PRRSV vaccination of piglets (Kritas et al, 2007;Mavromatis et al, 1999). It origin of the PRRSV genotype 2 strain is unknown.…”
Section: Discussionsupporting
confidence: 68%
“…The clinical protection was associated with a marked activation of the cell-mediated immune response. Similar results were shown by Mavromatis et al (1999). They demonstrated the protective property of a PRRSV live vaccine based on genotype 1 against the respiratory manifestation of PRRSV during the fattening period when the piglets were vaccinated in the 6th week of live.…”
Section: Introductionsupporting
confidence: 80%
“…Clinical signs of PRRSV infection in growing pigs include fever, sneezing, dyspnea, tachypnea, anorexia, and decreased weight gain. Vaccination is a common procedure to minimize economic losses associated with this pathogen, and vaccines have proven to be effective in experimental trials (33) and field studies (24,47). However, PRRSV vaccine failures are not uncommon in the field, and PRRSV continues to be the most common primary pathogen in cases of PRDC (18).…”
mentioning
confidence: 99%